Training Brazilian nurses to promote mental health at work - Miranda, Fernanda Maria de (2024)
Introduction: psychosocial risks are known problems in the context of hospital nursing work. Training leaders to promote mental health at work emerges as a powerful strategy, although still limited in the Brazilian context. Nurses' awareness of psychosocial risks and the workplace factors that affect them, as well as their position in the organization as nurse leaders, can strengthen the collective fight for healthy environments. Objective: to pilot a model to evaluate the effectiveness of a training intervention aimed at hospital nurse leaders to promote mental health at work. Method: pilot study with pre- and post-test in a single group with follow-up of two and four months after an online training called the Lidera-SMT Program, designed based on the Canadian National Standard of Psychological Workplace Health and Safety. The research was carried out in three stages: Development of the intervention and instruments; Validation of instrument content; Implementation and pilot and evaluation of Lidera-SMT. All nurses working in hospitals were eligible to participate in the intervention. The sample was non-probabilistic for convenience and those who did not complete the Program were excluded. Data were collected through a sociodemographic questionnaire and pilot testing the intervention was based on Donald Kirkpatrick's first three levels of evaluation, using as measures: level I – interest, confidence, attention, expectation; level II – learning; and level III – attitudes and perceived structural empowerment. Analysis used JAMOVI software and included descriptive statistics for participant characteristics; Non-parametric ANOVA, linear mixed model to assess learning retention; Cronbach's alpha to measure the internal consistency of the questionnaires; Spearman correlation test to identify correlation between attitudes and structural empowerment; and Mann-Whitney test to compare groups by training hours. The significance adopted was 5%. Ethical aspects were respected and the project was approved (Brazil: approval n. 5.627.685; CAAE 57917922.9.0000.5504; Canada: n. 1469900). Results: Lidera-SMT was based on the flipped classroom and was composed of four mandatory modules and one optional, totaling 8 or 10 hours. The sociodemographic questionnaire, the learning test and the perceived attitudes instrument, which were not validated, underwent validation using the Delphi Technique. Twelve Brazilian experts participated (eight academics and four nursing specialists). Lidera-SMT was implemented between July and August 2023. Sixty-seven nurses started the Program and 54 completed it, demonstrating 81% adherence. Both partial (n=50) and complete data (n=29) were considered to evaluate learning and behavior levels. Level I: satisfaction means above 4.46 (SD=0.872), with 94% of participants (n=50) over the cutoff point. Level II: mean score increased from 3.9 (pre) to 4.41 (2nd follow-up), with significant differences pre and post (p=0.04) and pre and 2nd follow-up (p<0.01). Level III: perceived attitudes achieved high scores, although no significant differences were observed between the assessment moments. The perception of structural empowerment has increased significantly. There are correlations between attitudes and structural empowerment. Conclusions: in pilot work, Lidera-SMT demonstrated to be an effective intervention for promoting mental health at work.